Characterization of Calcium-Dependent Protein Kinase 2A, a Potential Drug Target Against Cryptosporidiosis - Shu, Fanfan; Li, Yu; Chu, Wenlun; Chen, Xuehua; Zhang, Ziding; Guo, Yaqiong; Feng, Yaoyu; Xiao, Lihua; Li, Na (Frontiers in Microbiology, 2022)
Calcium-dependent protein kinases (CDPKs) are important in calcium influx, triggering several biological processes in Cryptosporidium spp. As they are not present in mammals, CDPKs are considered promising drug targets. Recent studies have characterized CpCDPK1, CpCDPK3, CpCDPK4, CpCDPK5, CpCDPK6 and CpCDPK9, but the role of CpCPK2A remains unclear. In this work, we expressed recombinant CpCDPK2A encoded by the cgd2_1060 gene in Escherichia coli, and characterized the biologic functions of CpCDPK2A using qRT-PCR, immunofluorescence microscopy, immuno-electron microscopy, and in vitro neutralization. The results revealed that CpCDPK2A protein was highly expressed in the apical region of sporozoites and merozoites and in macrogamonts. Monoclonal or polyclonal antibodies against CpCDPK2A failed to block the invasion of host cells. Among the 44 candidate inhibitors from molecular docking of CpCDPK2A, one inhibitor was identified as having a potential effect on both C. parvum growth and CpCDPK2A enzyme activities. These data suggest that CpCDPK2A may play some roles during the development of C. parvum and might be a potential drug target against cryptosporidiosis.